Relações dialógicas na obra “O Jogo do Pensamento”, de Vivina de Assis Viana - Rodrigues, Viviane Santiago Couto (2018)
This work has as its theme the analysis of dialogical relations in the novel The Game of Thought by Vivina de Assis Viana. This work is chosen, of juvenile literary art, in view of its importance for the emotional, social and cognitive development of the audience to which it is directed. The novel that constitutes the corpus of this research will be analyzed under the Bakhtinian view, which considers that the romanesque genre is an internal stratification of language, revealing the social diversity and divergence of social voices that it contains, as a plurilingual phenomenon , plurivocal and plurstilístico. The objective of the research is to analyze how the dialogue and the dialogic relations that take place in the development of the plot of this narrative are given. It is hoped by this analysis to verify if the work is based on the Bakhtinian thought on the ideological creation, the otherness, the soliloquy and the speech of another, in order to prove that this novel is not only a representation of itself, but also of the culture to which it is linked, as Bakhtin discovered about the novel in general. In order to reach the proposed objectives, the reflections on Bakhtin (1998, 2013), on the novel and the dialogism as well as the studies of commentators of his work, such as Brait (2005, 2010), Fiorin (2006) , Morson and Emerson (2008), Moisés (1973), among others. It was verified that the corpus is constituted dialogically in its narrative through soliloquy, which is based on an internal discourse, in which the character seeks his inner self and, through the discourse of others, presenting fragments discursives of other subjectivities than that of the narrator himself. The author, through the interrelationship of soliloquy and the discourse of others, used these linguistic resources to bring the reader closer to the point of view of the characters in relation to the game of thinking, which alludes indirectly to the "Game of life" in the process of identity construction of the postmodern subject. These forms of articulation contributed both to the attribution of important meanings and to the understanding of the narrative in the literary text.